Structural and Functional Characterization of a Novel Scorpion Toxin that Inhibits NaV1.8 via Interactions With the DI Voltage Sensor and DII Pore Module - George, Kiran; Lopez-Mateos, Diego; Abd El-Aziz, Tarek Mohamed; Xiao, Yucheng; Kline, Jake; Bao, Hong; Raza, Syed; Stockand, James D.; Cummins, Theodore R.; Fornelli, Luca; Rowe, Matthew P.; Yarov-Yarovoy, Vladimir; et al. (Frontiers in Pharmacology, 2022)
Voltage-gated sodium channel NaV1.8 regulates transmission of pain signals to the brain. While NaV1.8 has the potential to serve as a drug target, the molecular mechanisms that shape NaV1.8 gating are not completely understood, particularly mechanisms that couple activation to inactivation. Interactions between toxin producing animals and their predators provide a novel approach for investigating NaV structure-function relationships. Arizona bark scorpions produce Na+ channel toxins that initiate pain signaling. However, in predatory grasshopper mice, toxins inhibit NaV1.8 currents and block pain signals. A screen of synthetic peptide toxins predicted from bark scorpion venom showed that peptide NaTx36 inhibited Na+ current recorded from a recombinant grasshopper mouse NaV1.8 channel (OtNaV1.8). Toxin NaTx36 hyperpolarized OtNaV1.8 activation, steady-state fast inactivation, and slow inactivation. Mutagenesis revealed that the first gating charge in the domain I (DI) S4 voltage sensor and an acidic amino acid (E) in the DII SS2 – S6 pore loop are critical for the inhibitory effects of NaTx36. Computational modeling showed that a DI S1 – S2 asparagine (N) stabilizes the NaTx36 – OtNaV1.8 complex while residues in the DI S3 – S4 linker and S4 voltage sensor form electrostatic interactions that allow a toxin glutamine (Q) to contact the first S4 gating charge. Surprisingly, the models predicted that NaTx36 contacts amino acids in the DII S5 – SS1 pore loop instead of the SS2 – S6 loop; the DII SS2 – S6 loop motif (QVSE) alters the conformation of the DII S5 – SS1 pore loop, enhancing allosteric interactions between toxin and the DII S5 – SS1 pore loop. Few toxins have been identified that modify NaV1.8 gating. Moreover, few toxins have been described that modify sodium channel gating via the DI S4 voltage sensor. Thus, NaTx36 and OtNaV1.8 provide tools for investigating the structure-activity relationship between channel activation and inactivation gating, and the connection to alternative pain phenotypes.